Religious Leaders’ Roles in the Clean and Healthy Living Behavior Campaign - Wahyudin, Uud; Bajari, Atwar; Rumawan Erlandia, Dedi (International Journal of Psychosocial Rehabilitation, 2019)
The involvement of religious leaders in conducting the campaign of clean and healthy living behavior in Central Jampang Sub District, Sukabumi District, West Java, Indonesia has important roles in forming the healthy and clean living culture. They can assist the government to make people in this area change their behavior because the people have not possesed the habit to live healthily and cleanly. Distinctive with any other representatives of civil society, religious leaders have the experience of establishing and creating relationship. Therefore, this study was aimed at examining the characteristic factors and roles level of religious leaders in conducting the campaign. The methods used are correlational by testing the relationship between two variables. The population of study is all the religious leaders who live in Jampang, West Java, Indonesia. The data collection technique was done by distributing questionnaires to the respondents. The number of samples are 92 respondents. The results showed that the religious leaders’ roles as communicator, motivator, mediator, and legitimator in the communication campaign of healthy living possess high level. There is also a positive relationship between their characteristics factors and their roles level.